The Geographic Dispersion of Aboriginals in Quebec and Its Economic Limitations - Ramsay, Charles-Albert (Journal of Aboriginal Economic Development, 2017)
This paper discusses the state of economic activity in Aboriginal Quebec, Canada, focusing on the size of settlements both on-reserve and off-reserve. Size is an important variable in understanding the economic possibilities of a community. Data is also presented for off-reserve Aboriginals living in big cities and in smaller towns.Findings show there are relatively few Indigenous people in Quebec and that they are scattered across many distinct nations. Most Indigenous people on-reserve live in very small settlements. Most towns in Quebec hold an Indigenous community, albeit not necessarily visible. Most Indigenous people off-reserve live in larger centres (Greater Montreal, Gatineau, Quebec City). The Outaouais region, on the north-shore of the Ottawa River, is a unique part of Quebec with its high percentage of Indigenous populations living off-reserve.